Optimalisasi Pengelolaan Sampah melalui Tong Sampah Edukatif dan Pemilahan Limbah di Desa Waled Kabupaten Cirebon - Leni Rohida; Siti Adha Aulawiyah; Aisyah Nurul Azizah; Jihan Fathonah; Bunga Destra Lestari; Azra Zivana Zaneta (STIKES Columbia Asia Medan, 2026)
Waste management remains a pressing environmental issue, particularly in tourist areas with high visitor traffic. This situation is evident in the tourist area of ​​Waled Village, Cirebon Regency, which faces challenges regarding waste accumulation and inadequate facilities for waste sorting. This community service initiative aims to improve waste management effectiveness by providing educational sorting facilities and fostering awareness among the community and visitors regarding proper waste categorization. The project was implemented in several stages: assessing cleanliness conditions through observation; constructing sorting bins from large, repurposed paint buckets; applying color-coding and educational labels; creating informational banners; installing these educational facilities in the tourist area; and organizing a community cleanup event. Data were analyzed using a descriptive-qualitative approach based on observations and documentation gathered during the program. The results indicate that the entire program was executed according to plan, evidenced by the installation of three sorting bins and an educational banner, as well as the successful conduct of the community cleanup. The use of bins with visual identifiers for organic, inorganic, and hazardous/toxic (B3) waste categories provided visitors with easily understandable information for sorting waste. Furthermore, community involvement in the cleanup activity demonstrated a positive response and active participation in maintaining the cleanliness of the tourist area. Thus, utilizing simple facilities combined with environmental education serves as an effective approach to supporting waste management and creating a cleaner, more comfortable, and sustainable rural tourist destination.Waste management remains a pressing environmental issue, particularly in tourist areas with high visitor traffic. This situation is evident in the tourist area of ​​Waled Village, Cirebon Regency, which faces challenges regarding waste accumulation and inadequate facilities for waste sorting. This community service initiative aims to improve waste management effectiveness by providing educational sorting facilities and fostering awareness among the community and visitors regarding proper waste categorization. The project was implemented in several stages: assessing cleanliness conditions through observation; constructing sorting bins from large, repurposed paint buckets; applying color-coding and educational labels; creating informational banners; installing these educational facilities in the tourist area; and organizing a community cleanup event. Data were analyzed using a descriptive-qualitative approach based on observations and documentation gathered during the program. The results indicate that the entire program was executed according to plan, evidenced by the installation of three sorting bins and an educational banner, as well as the successful conduct of the community cleanup. The use of bins with visual identifiers for organic, inorganic, and hazardous/toxic (B3) waste categories provided visitors with easily understandable information for sorting waste. Furthermore, community involvement in the cleanup activity demonstrated a positive response and active participation in maintaining the cleanliness of the tourist area. Thus, utilizing simple facilities combined with environmental education serves as an effective approach to supporting waste management and creating a cleaner, more comfortable, and sustainable rural tourist destination.